ARID1A Mutation in Metastatic Breast Cancer: A Potential Therapeutic Target - Cheng, Xuan; Zhao, Jian-Xiong; Dong, Feng; Cao, Xu-Chen (Frontiers in Oncology, 2021)
Distant metastasis is the principal cause of mortality for breast cancer patients. Targeting specific mutations that have been acquired during the evolution process of advanced breast cancer is a potential means of enhancing the clinical efficacy of treatment strategies. In metastatic breast cancer, ARID1A is the most prevalent mutation of the SWI/SNF complex, which regulates DNA repair, recombination, and gene transcription. The low expression of ARID1A is associated with poor disease-free survival and overall survival of patients with luminal A or HER2-rich breast cancer. In addition, ARID1A plays a prominent role in maintaining luminal characteristics and has an advantage for identifying responses to treatment, including endocrine therapies, HDAC inhibitors and CDK4/6 inhibitors. Therapeutic vulnerabilities initiated by ARID1A alterations encourage us to explore new approaches to cope with ARID1A mutant-related drug resistance or metastasis. In this review, we describe the mutation profiles of ARID1A in metastatic breast cancer, the structure and function of ARID1A and the SWI/SNF complex, as well as discuss potential mechanisms of ARID1A-mediated endocrine resistance and therapeutic potential.